A polyetheramine modified layered silicate and its preparation method and application

By combining polyetheramine with 2:1 type layered silicate, a polyetheramine-modified layered silicate with high adsorption capacity and cycle stability is prepared, which solves the problem of existing carbon dioxide capture materials in the recycling process. The problem of poor stability.

CN118788313BActive Publication Date: 2025-01-24SHANDONG HAIHUA GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411261337.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-24
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing carbon dioxide capture materials have problems with high adsorption amount but poor stability during the circulation process, especially when polymer amine materials are prone to decomposition and dissociation during the heating and cooling cycle, resulting in a degradation of performance.

Method used

Polyetheramine is used as the amination agent and combined with the layered silicate with a 2:1 structure. Polyetheramine modified layered silicate is prepared through ultrasonic dispersion and high-temperature hydrothermal reaction to form a polyetheramine-modified layered silicate with high specific surface area and Pore ​​capacity of the material.

Benefits of technology

It achieves efficient adsorption of carbon dioxide and maintains 98.1%-99% adsorption capacity in multiple cycles, significantly improving the cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118788313B_ABST
    Figure CN118788313B_ABST
Patent Text Reader

Abstract

The invention discloses a polyetheramine modified layered silicate and a preparation method and application thereof, belonging to the technical field of preparation and application of modified silicate materials. A natural or chemically synthesized layered silicate with a 2:1 structure is used as an inorganic carrier, polyetheramine is used as an organic aminating agent, the mass ratio of layered silicate, polyetheramine and deionized water is controlled to be 10:2.5~5:50~100, the mixed liquid is ultrasonically dispersed and then hydrothermally stirred at 180-300°C for 2-4h, and then solid-liquid separation and drying treatment are performed to finally obtain a polyetheramine modified layered silicate with a high specific surface area and high pore capacity, the preparation process is simple, the cost of the inorganic carrier is low, it is suitable for industrial-scale production, and it is particularly suitable for adsorbing and capturing acidic gases such as carbon dioxide, with high adsorption capacity and high cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation and application of modified silicate materials, and in particular to a polyetheramine modified layered silicate and a preparation method and application thereof. Background Art

[0002] As a supporting technology for achieving the "dual carbon" goals, research on carbon dioxide capture technology has developed rapidly in recent years. Among them, the most popular adsorption and capture materials are amine functionalized modified materials, and the research focuses on the carrier, aminating agent and the combination of the two.

[0003] Compared with organic carriers, inorganic carriers have many types, rich sources of raw materials, high stability, and obvious cost advantages. At present, mesoporous materials, including MCM-41, mesoporous carbon, mesoporous alumina, etc., are more studied. Their preparation process is relatively complicated, and their binding ability with organic aminating agents is poor, and the prospect of large-scale application is worrying. As for aminating agents, the main problem currently exists that organic amine compounds with small molecular weight and low degree of branching, such as monoethanolamine and diethyltriamine, will have different degrees of leaching, degradation and volatilization during the circulation process, while amines with high degree of branching and high molecular weight, such as polyethyleneimine, which is widely used, have low binding strength with inorganic carriers. In the process of multiple cycles of adsorption and desorption, heating and cooling, polyethyleneimine is easy to decompose and dissociate. Although the adsorption amount is high, the cyclic stability is poor.

[0004] There are three main ways to combine aminating agents and carriers: impregnation, grafting and in-situ polymerization. The impregnation method loads the organic aminating agent on the surface and pores of the carrier. The surface groups, heteroatom doping and the size of the pores will affect the capture performance. The diffusion barrier caused by pore blockage will significantly reduce the capture efficiency. The problem with the grafting method is that the local surface environment of the former carrier and the distance of the bridge will affect the capture performance. The in-situ polymerization method is to combine the carrier and the aminating agent during the synthesis process of the carrier or the aminating agent. The material obtained by this method has high stability, but there are few research reports at present. The Chinese patent document with publication number CN115318262A discloses an amine-functionalized silicon-based adsorbent and its preparation method and application. Polyethyleneimine is used as the aminating agent. The aminated silicon-based adsorbent material is prepared by in-situ polymerization. It has a high adsorption capacity and achieves a good capture effect. However, it uses more reagents, has complex process steps, has a high carrier cost, and has a significant performance decline after multiple cycles, and the prospect of large-scale application is poor. Summary of the invention

[0005] The purpose of the present invention is to provide a polyetheramine-modified layered silicate and a preparation method and application thereof. The preparation process of the polyetheramine-modified layered silicate provided by the present invention is simple, the cost of the inorganic carrier is low, and the obtained polyetheramine-modified layered silicate has a high adsorption capacity and strong cyclic stability, and is particularly suitable for adsorbing and capturing carbon dioxide.

[0006] The technical solution of the present invention is:

[0007] The first object of the present invention is to provide a method for preparing polyetheramine-modified layered silicate, which effectively combines layered silicate with polyetheramine by ultrasonic dispersion and high-temperature hydrothermal reaction.

[0008] Furthermore, the preparation method comprises:

[0009] Step 1: Mix the layered silicate with a 2:1 structure, polyetheramine and deionized water, and perform ultrasonic dispersion to obtain a dispersion A;

[0010] Step 2: Under closed conditions, the dispersion A is heated to react to obtain a suspension B, which is filtered, separated, and dried to obtain a polyetheramine-modified layered silicate.

[0011] Preferably, the mass ratio of the layered silicate, polyetheramine and deionized water is controlled at 10:2.5~5:50~100. If the amount of polyetheramine added is too little, there will be fewer amino groups between the layers of the polyetheramine-modified layered silicate, and fewer sites that can bind to carbon dioxide, resulting in a weakened adsorption capacity for carbon dioxide; if the amount of polyetheramine added is too much, it will block the pores of the inorganic carrier, making it difficult for carbon dioxide to enter the interior, and also resulting in a weakened adsorption capacity of the polyetheramine-modified layered silicate for carbon dioxide. The increase in the amount of polyetheramine will also increase the cost. The proportion of water is controlled mainly to ensure the dispersion effect of the dispersion. Adding too little water will result in uneven dispersion of the polyetheramine and silicate, while adding too much water will make the solution too dilute, reducing the reaction mass transfer efficiency.

[0012] Preferably, the layered silicate is a layered silicate with a 2:1 structure, including any one of montmorillonite, talc, sepiolite, magnesium silicate, lithium magnesium silicate, and aluminum magnesium silicate. Montmorillonite, talc, and sepiolite are natural clay minerals that already exist in nature, and magnesium silicate, lithium magnesium silicate, and aluminum magnesium silicate are generally silicates obtained by artificial chemical synthesis. These layered silicates are cheap and do not require additional treatment before use, but if they are subjected to conventional technical treatments such as purification, acidification, and grinding before use, as long as the 2:1 structure of the layered silicate is unchanged, they should also belong to the protection scope of this patent.

[0013] Preferably, the dispersion is performed using ultrasound, the frequency of the ultrasound is 50-90 kHz, and the ultrasound time is 20-50 min.

[0014] Preferably, the heating reaction is carried out in a closed reactor, wherein the reaction temperature is 180-300°C, and the reaction time is 2-4 hours. The preferred reaction temperature is 220-260°C.

[0015] Preferably, the drying includes atmospheric pressure drying, vacuum drying, flash drying, preferably flash drying, the drying temperature is 100-200°C, preferably 140-160°C, while ensuring that moisture and impurities are completely removed, the drying time is shortened as much as possible, so as to ensure that the rich pore structure is not destroyed.

[0016] The second object of the present invention is to provide a polyetheramine modified layered silicate obtained by the above preparation method, having a molecular weight of 489-550m 2 / g specific surface area, 0.92-1.55cm 3 / g pore capacity.

[0017] The third object of the present invention is to provide an application of the above material, wherein the polyetheramine-modified layered silicate is used for adsorption and capture of carbon dioxide.

[0018] Working principle: Layered silicate is a type of silicate with a layered structure. It is abundant in source and has low preparation cost. Its layered structure is divided into 1:1 type and 2:1 type. The layered silicate with 2:1 structure has rich interlayer charge and is used as a modified carrier. The modified molecules can enter the interlayer to play a role. Polyetheramine is an amino-terminated polyether with excellent performance. The structural formula is CH3CH(NH2)CH2[OCH2CH(CH3)]nNH2. The 2:1 layered structure of the inorganic silicate carrier provides abundant interlayer space and pores. Carbon dioxide can easily enter at room temperature by physical adsorption. After entering, it chemically combines with the amino group of polyetheramine. This physical adsorption and chemical combination will weaken when the temperature is increased, so that carbon dioxide can be desorbed from the interlayer space and pores by increasing the temperature. In this way, carbon dioxide can be captured and collected by temperature-swing adsorption; combining polyetheramine with layered silicate to prepare polyetheramine-modified layered silicate will be an effective way to solve the current application problems of carbon dioxide adsorption and capture materials and overcome the contradiction between high adsorption capacity and high stability.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] (1) The present invention uses polyetheramine as an aminating agent. Polyetheramine contains ether bonds and has higher polarity and thermal stability than other polymer amines. The chemical bond between the ether bond and the silicate carrier is strong and is not easily decomposed and lost during temperature changes, thereby improving the stability of the material.

[0021] (2) The present invention uses a 2:1 type layered silicate as an inorganic carrier. Compared with other inorganic carriers, the 2:1 type layered silicate can provide more binding space for polyetheramine. The polyetheramine inserted between the inorganic silicate layers is not easy to dissociate when the temperature rises, which improves the cyclic stability of the material. After 10 cycles, the adsorption amount can still maintain the initial 98.1%-99%.

[0022] (3) The present invention adopts an optimized raw material addition ratio to make the polyetheramine-modified layered silicate have a higher specific surface area and pore capacity. The appropriate amount of polyetheramine added will not affect the pores of the layered silicate, and can provide sufficient adsorption sites, so that the adsorption material has a high adsorption capacity of 3.88-4.8mmol / g, and also has high cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The fitting curve of the specific surface area analysis test of polyetheramine modified layered silicate;

[0024] Figure 2 Infrared spectrum of polyetheramine modified layered silicate 1000-1500cm -1 curve. DETAILED DESCRIPTION

[0025] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0026] The technical solutions provided by the present invention will be described clearly and completely below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0027] This embodiment provides a method for preparing a polyetheramine-modified layered silicate, which is as follows:

[0028] 50 g of magnesium silicate and 25 g of polyetheramine were added to 500 g of water and mixed, with the mass ratio of magnesium silicate, polyetheramine and deionized water being 10:5:100. The mixture was ultrasonicated at 50 kHz for 20 min to obtain a uniform dispersion. The dispersion was then placed in a closed stirring reactor, reacted at 220° C. for 2 h, and then taken out to obtain a suspension. The solid separated by filtration was flash dried at 150° C. to obtain a polyetheramine-modified layered silicate, named S1. Example 2

[0029] This embodiment provides a method for preparing a polyetheramine-modified layered silicate, which is as follows:

[0030] 40 g of lithium magnesium silicate and 10 g of polyetheramine were added to 400 g of water and mixed, with the mass ratio of lithium magnesium silicate, polyetheramine and deionized water being 10:2.5:100. The mixture was ultrasonicated at 60 kHz for 30 min to obtain a uniform dispersion. The dispersion was then placed in a closed stirring reactor, reacted at 240° C. for 3 h, and then taken out to obtain a suspension. The solid separated by filtration was vacuum dried at 100° C. to obtain a polyetheramine-modified layered silicate, named S2. Example 3

[0031] This embodiment provides a method for preparing a polyetheramine-modified layered silicate, which is as follows:

[0032] 25 g of magnesium aluminum silicate and 10 g of polyetheramine were added to 150 g of water and mixed. The mass ratio of magnesium aluminum silicate, polyetheramine and deionized water was 10:4:60. Ultrasound was applied at 90 kHz for 40 min to obtain a uniform dispersion. The dispersion was then placed in a closed stirring reactor, reacted at 280° C. for 4 h, and then taken out to obtain a suspension. The solid separated by filtration was flash dried at 120° C. to obtain a polyetheramine-modified layered silicate, named S3. Example 4

[0033] This embodiment provides a method for preparing a polyetheramine-modified layered silicate, which is as follows:

[0034] 5 g of montmorillonite and 1.5 g of polyetheramine were added to 25 g of water and mixed. The mass ratio of montmorillonite, polyetheramine and deionized water was 10:3:50. Ultrasound was applied at 80 kHz for 30 min to obtain a uniform dispersion. The dispersion was then placed in a closed stirring reactor, reacted at 300° C. for 2 h, and then taken out to obtain a suspension. The solid separated by filtration was vacuum dried at 200° C. to obtain a polyetheramine-modified layered silicate, named S4. Example 5

[0035] This embodiment provides a method for preparing a polyetheramine-modified layered silicate, which is as follows:

[0036] 50 g of sepiolite and 17.5 g of polyetheramine were added to 400 g of water and mixed. The mass ratio of sepiolite, polyetheramine and deionized water was 10:3.5:80. Ultrasound was applied at 60 kHz for 20 min to obtain a uniform dispersion. The dispersion was then placed in a closed stirring reactor, reacted at 260° C. for 4 h, and then taken out to obtain a suspension. The solid separated by filtration was flash dried at 140° C. to obtain a polyetheramine-modified layered silicate, named S5. Example 6

[0037] This embodiment provides a method for preparing a polyetheramine-modified layered silicate, which is as follows:

[0038] 40 g of talc and 12 g of polyetheramine were added to 300 g of water and mixed. The mass ratio of talc, polyetheramine and deionized water was 10:3:75. Ultrasound was applied at 70 kHz for 50 min to obtain a uniform dispersion. The dispersion was then placed in a closed stirring reactor, reacted at 180° C. for 3 h, and then taken out to obtain a suspension. The solid separated by filtration was flash dried at 160° C. to obtain a polyetheramine-modified layered silicate, named S6. Comparative Example 1

[0039] This comparative example provides a method for preparing a polyetheramine-modified layered silicate. The preparation method is the same as Example 1 except that the amount of polyetheramine used is increased so that the addition ratio of magnesium silicate, polyetheramine and deionized water is 10:7.5:100, and the remaining steps and amounts are the same as those in Example 1 to obtain a polyetheramine-modified layered silicate named S7. Comparative Example 2

[0040] This comparative example provides a method for preparing a polyetheramine-modified layered silicate. The preparation method is the same as Example 1 except that magnesium silicate is replaced with kaolinite (1:1 layered structure), and the remaining steps and amounts are the same as those of Example 1 to obtain a polyetheramine-modified layered silicate named S8. Comparative Example 3

[0041] This comparative example provides a method for preparing polyethyleneimine-modified layered silicate. Except for replacing polyetheramine with polyethyleneimine, the remaining steps and amounts are the same as those in Example 1 to obtain polyethyleneimine-modified layered silicate, which is named S9. Comparative Example 4

[0042] This comparative example provides a magnesium silicate that has not been modified by amination, which is recorded as sample S10. Comparative Example 5

[0043] According to the review literature (Song Kechen, Cui Xili, Xing Huabin. Research Progress on Materials and Technologies for Direct Air Capture of Carbon Dioxide [J]. Chemical Industry Progress, 2022, 41(3):11.), as far as amine-functionalized inorganic materials are concerned, the carbon dioxide adsorption capacity of commercial silica adsorbents combined with polyethyleneimine is 2.36mmol / g, and the cycle adsorption retention rate is 70%. The carbon dioxide adsorption capacity of commercial mesoporous silica foam adsorbents combined with polyethyleneimine is 1.74mmol / g, and the cycle adsorption retention rate is 97.7%.

[0044] Test Example 1

[0045] Material structure analysis: Fourier transform infrared spectrometer was used to test samples S1-S6 of Examples 1-6, with a wave number range of 1000-1500 cm -1 (Ether bond characteristic peak range), and the attached Figure 2 The curve shown in Figure 1 shows the stretching vibration peak of the ether bond COC formed after the addition of polyetheramine at 1150-1060 cm -1 , indicating the effective combination of polyetheramine and layered silicate; the specific surface area and pore capacity of samples S1-S10 were measured by V-Sorb 2800P of Guoyi Precision Measurement, and the surface area and pore capacity of samples S1-S10 were measured after degassing at 120℃ for 2 hours, using nitrogen as the adsorption and desorption gas, and the adsorption Figure 1 The curve shown is calculated and analyzed using the BET multi-point test method. The single-layer adsorption amount is equal to the reciprocal of the sum of the intercept and slope of the fitting curve, and the specific surface area is equal to the product of 4.354 square meters and the single-layer adsorption amount. The relevant data are recorded in Table 1.

[0046] Test Example 2

[0047] Carbon dioxide adsorption test: First, samples S1-S10 are evenly arranged in a micro-fixed bed, and then a mixed gas containing carbon dioxide is circulated through the fixed bed at a rate of 400 mg / L to allow the mixed gas to fully contact the polyetheramine-modified layered silicate. The adsorption data is calculated based on the weight before and after and the change in the composition of the mixed gas. Then the fixed bed is heated to 120°C and maintained for 2 hours to allow carbon dioxide to desorb from the polyetheramine-modified layered silicate. The weight is measured again to calculate the data after desorption, and this is repeated 10 times. The relevant data are recorded in Table 1.

[0048]

[0049] In general, it can be seen from Table 1 that the specific surface area, pore capacity, adsorption amount and cycle stability (adsorption amount retention rate after 10 cycles) of samples S1-S6 with polyetheramine added are higher than those of samples S7-S10 without polyetheramine or with polyethyleneimine added.

[0050] Comparative Example 1 uses an excessive amount of polyetheramine, which will clog the pores, causing the specific surface area and pore capacity of sample S7 to be much lower than those of S1 with the same process, which in turn leads to a decrease in adsorption capacity and cycle stability.

[0051] Comparative Example 2 uses a silicate (kaolinite) that is not a 2:1 type structure as an inorganic carrier, which does not have a large structural space, and has a low specific surface area and pore capacity. At the same time, the smaller layer space also leads to a lower degree of binding with polyetheramine, and poor adsorption capacity and cyclic stability.

[0052] Comparative Example 3 uses polyethyleneimine as the aminating agent, which is the current mainstream method. The specific surface area and pore capacity of sample S9 are relatively close to those of the present invention. However, since it does not contain ether bonds, compared with polyetheramine, its bonding strength with the inorganic carrier is lower, and it is easily decomposed and lost during temperature changes, resulting in poor stability after multiple cycles.

[0053] Comparative Example 4 uses magnesium silicate without adding an aminating agent but only with an inorganic carrier. It can be seen that S10 has a certain specific surface area and pore capacity, but due to the lack of amination modification, it cannot chemically bond with carbon dioxide, and its ability to adsorb carbon dioxide is weak. It relies solely on physical adsorption and is greatly affected by temperature fluctuations, resulting in a low adsorption amount and low adsorption stability.

[0054] Comparative Example 5 is some data of the prior art and literature using silicon-based inorganic aminated materials. By comparison, it can be found that the adsorption capacity of 3.88-4.8 mmol / g and the cycle stability of 98.1-99% of the present invention are better than 2.36 mmol / g and 97.7% of the prior art.

[0055] In summary, compared with the prior art, the polyetheramine-modified phyllosilicate of the present invention achieves both a high carbon dioxide adsorption capacity and extremely high cycle stability. The polyetheramine-modified phyllosilicate provided by the present invention and its preparation method and application have the characteristics of simplified and efficient preparation process, low price of inorganic carrier, high carbon dioxide adsorption capacity, high cycle stability, excellent comprehensive performance, and are suitable for industrial-scale production.

[0056] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a polyetheramine-modified layered silicate, characterized in that: Step 1: Mix the layered silicate with a 2:1 structure, polyetheramine and deionized water in a mass ratio of 10:2.5-5:50-100, and perform ultrasonic dispersion to obtain a dispersion A; Step 2: Under closed conditions, the dispersion A is heated to react at 180-300°C for 2-4 hours to obtain a suspension B, which is filtered, separated, and dried to obtain a polyetheramine-modified layered silicate.

2. The method for preparing the polyetheramine-modified layered silicate according to claim 1, characterized in that: The layered silicate includes any one of montmorillonite, talc, sepiolite, magnesium silicate, lithium magnesium silicate or aluminum magnesium silicate.

3. The method for preparing the polyetheramine-modified layered silicate according to claim 1, characterized in that: The drying includes any one of normal pressure drying, vacuum drying or flash drying, and the drying temperature is 100-200°C.

4. A polyetheramine-modified layered silicate, characterized in that: The polyetheramine modified layered silicate is prepared according to the method described in any one of claims 1 to 3, and has a specific surface area ranging from 489 to 550 m 2 / g, pore capacity range is 0.92-1.55cm 3 / g.

5. An application of the polyetheramine-modified layered silicate as claimed in claim 4, characterized in that: The polyetheramine-modified layered silicate is used for adsorption and capture of carbon dioxide.

Citation Information

Patent Citations

  • Amine-functionalized silicon-based adsorbent as well as preparation method and application thereof

    CN115318262A

  • Preparation method and application of CO2 adsorbent

    CN111514857A